Vital Sign Monitoring in ICU Patients Based on MEWS (Modified Early Warning Score) with IOT (Internet of Things) - Agus Sukarno; Arief Marwanto; Suryani Alifah (Universitas Islam Sultan Agung, 2020)
Vital signs are signs that show important functions of the human body, from these signs can be known whether a person is relatively healthy, has a serious illness, or suffers from a life-threatening disorder. Vital signs are the value of physiological functions consisting of blood pressure, temperature, oxygen saturation, pulse and respiratory rate. Vital sign monitoring tools researchers used four parameters, namely blood preasure, heart rate, oxygen saturation, and body temperature. The tool uses the IoT (Internet of Things) system, where this tool uses sensors used, namely the DS18B20 temperature sensor, the Heart Rate sensor and the SPO2 MAX 30100 sensor, the OMRON HME-7130 sensor, the ESP 32 microcontroller as a data processor and Wi-Fi connection. The patient's vital condition data will be displayed on the android smartphone and on the mydevices.com WEB page. This tool is rule-based with a Modified Early Warning Score (MEWS) system to determine the status of patients and assist medical personnel in monitoring the vital parameters of patient signs in real time at each location and responding quickly and precisely so as to improve the quality of life of patients. Comparison using patient monitor tools, body temperature measurements produce the highest and lowest percentage of error that is 0.19% and 0.08% with an average temperature of 36.06ºC and 35.96ºC, then heart rate measurements obtained the highest and lowest percentage of errors of 0.08% and 0.3% with an average heart rate of 74 bpm and 87.3. Then the measurement of SpO2 obtained the highest and lowest percentage of error of 1% and 0% with an average SpO2 of 97% and 97.3%, then the NIBP measurement obtained the highest and lowest percentage of error systole / diastole of 7.4% / 7.2% with NIBP with an average systole / diastole of 109.6 / 64 mmHg and the lowest error percentage is 0.3% / 1.1% with an average NIBP of 125 / 62.3 mmHg. Data transmission to the internet using the cayene application on Android smartphones and WEB is greatly influenced by the quality of the connection from the internet network. Key words: Vital Signs, Modified Early Warning Score (MEWS), DS18B20, MAX 30100, ESP32 Microcontroller, IoT.